Model of using cloud-based environment in training databases of future IT specialists - Olha V. Korotun; Tetiana A. Vakaliuk; Vladimir N. Soloviev (Academy of Cognitive and Natural Sciences, 2020)
The authors substantiates and develops the model of using cloud-based environment (CBE) in the training of databases of future information technology (IT) specialists, which consists of interrelated units: target (purpose, task of using CBE), conceptual (pedagogical approaches, didactic principles), organizational and semantic (characteristics of CBE, basic requirements for CBE, subjects of training, CBE of the teacher, CBE of the student, curricula of institution of higher education, educational-methodical complex of discipline "Databases", installation and configuration of database management system, development of educational material from the database in electronic form, selection of cloudbased systems of distance learning, introduction of cloud-based systems of distance learning in the training of students' databases, selection of CBE in database training (databases, forms, methods, tools), evaluative (criteria, indicators, levels of professional and practical competence of future IT specialists on the use of CBE in database training), effective (increased formation of the information and communication technologies of future IT specialists on the use of CBE in database training).